Attacks Intended to Seriously Harm and Co-occurring Drug Use Among Youth in the United States. (9th November 2016) - Salas-Wright, Christopher P.; Vaughn, Michael G.; Reingle Gonzalez, Jennifer M.; Fu, Qiang; Clark Goings, Trenette
ABSTRACT: Background : While it is known that substance use and violence co-occur, less is understood in terms of how this relationship might vary based on the degree of youth involvement in violence. Objectives : This study sought to examine the prevalence and degree that substance use disorders (SUD) and related intrapersonal and contextual factors were associated with violent attacks. Method : Repeated cross-sectional data from a population-based study (National Survey on Drug Use and Health) of youth ages 12–17 ( n = 216, 852) in the United States between 2002 and 2013 were pooled to increase the analytic sample size. Survey multinomial regression was used to examine psychosocial and substance use differences between youth reporting episodic (1–2 times, n = 13, 091; 5.84%) and repeated violent attacks (3+ times, n = 1, 819; 0.83%) in contrast with youth reporting no attacks. Additional analyses examined the association of sociodemographic, intrapersonal, and contextual factors with SUD among youth reporting violent attacks. Results : The prevalence of SUD among youth with no attacks was 6% compared to 22% among episodic and 36% among repeatedly violent youth. Violence-involved youth were substantially more likely to experience elevated sensation-seeking, easy drug access, and recent drug offers and less likely to benefit from religiosity and protective substance use beliefs. Conclusions/Importance : Findings highlight the importance of distinguishing between the various gradations of violence among youth in understanding the relationship between substance use and violence, and shed light on the intrapersonal and contextual factors that can help identify violent youth at greatest risk for substance use problems.